Development National Ethical Framework for AI Use in Indonesia: Perspectives Regulation and Socio-Cultural Values - Ramadhan, Fatih Humam; Munawaroh, Siti (Journal of Artificial Intelligence Research, 2025)
Development rapidly intelligence Artificial Intelligence (AI) brings impact big to various sector life , but at a time cause challenge complex ethics , especially in developing countries like Indonesia. Until moment this , Indonesia has not own framework ethics national regulation​ the use of AI in comprehensive and contextual research​ This aim For develop framework ethics national that is not only based on the principles global ethics , but also in harmony with values Indonesian social and cultural methods research used​ is qualitative exploratory , with technique data collection in the form of interview deep against 20 informants key , study documentation and observation literature . Data analyzed use approach analysis Miles & Huberman's thematic research results show that five principles the main thing that is considered priority in framework national AI ethics is transparency , fairness , privacy , responsibility answer , and suitability with mark local . The findings also revealed existence asynchrony between existing digital regulations with need protection ethics in use of AI. Therefore that , the framework proposed ethics​ consists of from six component main ones that include principle basic , standard technical , governance institutions , supervision public , literacy ethics and harmonization international research​ This confirm importance approach contextual and participatory in formulate responsible AI policy responsible , inclusive , and sustainable in Indonesia.